Faktor-Faktor Yang Mempengaruhi Perilaku Pengelolaan Keuangan: Studi Empiris Pada Mahasiswa Akuntansi Universitas Pat Petulai - Tika Oktarina, Tika; Sucipto Febrianto (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
This research aims to empirically determine the relationship between financial literacy, pocket money, lifestyle, gender and level of education and financial management behavior. This research was conducted by taking a sample of UPP Accounting students in Rejang Lebong Regency, Curup City. The theory used in this research is the TPB theory. The number of samples selected was 60, with research results namely that financial literacy, lifestyle, gender and education level did not have a partial relationship with financial management behavior. Meanwhile, pocket money has a partial relationship with financial management behavior. However, simultaneously the five variables, namely financial literacy, pocket money, lifestyle, gender and education level have a relationship with financial management behavior.